2020
DOI: 10.22219/jpbi.v6i2.11370
|View full text |Cite
|
Sign up to set email alerts
|

Interactive multimedia: Enhacing students’ cognitive learning and creative thinking skill in Arthropod material

Abstract: Interactive multimedia based on Adobe Director, as a learning medium, is important in optimizing students’ learning outcomes. This study aimed to develop interactive multimedia in Arthropod topic as a learning media based on Adobe Director in optimizing students’ cognitive learning outcomes as well as their creative thinking skills. This Research and Development (R & D) adopted Borg & Gall model. The validity of the media developed was assessed by material and media experts. The product trial was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…It can be concluded that the level of creativity of students using the basic interactive media of Graphic Design is included in the category of high creativity. This is in line with previous studies [12], [13].…”
Section: Test Results Datasupporting
confidence: 94%
“…It can be concluded that the level of creativity of students using the basic interactive media of Graphic Design is included in the category of high creativity. This is in line with previous studies [12], [13].…”
Section: Test Results Datasupporting
confidence: 94%
“…Thus, based on the result of independents sample t-Test analysis, there are an indication that the mDPBL teaching approach for teaching strategy is contribute to students' creative thinking development. In the other word, multimedia learning helps improving students' creative thinking skill (Darmawan et al, 2020;Hermita et al, 2022).…”
Section: Discussionmentioning
confidence: 99%